Analysis of Factors Influencing Consumer Decisions in Coffee Shops in Asahan Regency Is - Rizky Hafrizany SP; Zulkarnain Lubis; Syahbudin Hasibuan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the key factors influencing consumer decision-making in the context of coffeeshops, focusing on six prominent establishments in Asahan Regency: Kaulamuda Coffee Space, Orion Coffee Space, Teha Coffee Corner, Beans Bottle Coffee, Semakin.Co, and Hening.Co. The research area was selected purposively, while the sample size of 285 respondents was determined using Slovin’s formula. A proportionate stratified random sampling technique was applied, combined with accidental sampling for respondent selection. Data were analyzed using multiple linear regression. The empirical findings reveal that price, product quality, location, social media, service quality, and promotion collectively have a significant influence on consumer decision-making. However, partially, social media was found to have no statistically significant effect. These findings highlight the multifaceted nature of consumer behavior and offer practical insights for marketing strategies in the coffee shop industry.